People and Nature in Asian Stories: Reading and Writing Materials for Eco Education - Novita Dewi (kata, 2017)
The purpose of this article is to make parents/teachers/writers of children literature aware of eco education through stories about people and nature. Written through the eyes of a child, many conservation stories not only empower the young minds, but they also help adults change their attitude to respect environment. The first part of this article examines such environmental stories as fables, folklores, short stories from Asia, while the second part is a project report on writing eco education materials, i.e. a serial of 3 environmental stories for young adults. Using Ecocriticism and Postcolonial perspectives to analyze the stories, the study shows that the narrative strands found in the stories include (1) depletion of the earth and natural resources, (2) people’s greediness, and (3) preservation of the traditional wisdom. Some stories are still anthropocentric so as to provide no space to explore fully the human-nature relationship in a balanced way. Although animal stories dominate the narratives, it is the specific and philosophic depiction of place and nature that give the stories Asian characteristics in their shared campaign to save our planet. This study concludes that the call for environmental protection can be done through young adult literature in a non-condescending manner instead of the usual patronizing-colonizing method